Mutualisms within light microhabitats are associated with sensory convergence in a mimetic butterfly community - J. Benito Wainwright; Theodora Loupasaki; Francisco Ramírez; Iestyn L. Penry-Williams; Sam J. England; Annalie Barker; Joana I. Meier; Martin J. How; Nicholas W. Roberts; Jolyon Troscianko; Stephen H. Montgomery (Proceedings of the National Academy of Sciences, 2025)
Niche partitioning within variable habitats can expose species to distinct sensory information. Vision is the primary sensory modality used by many animals to interact with their habitat. However, the role of terrestrial light environment properties in shaping species assemblages and visual system evolution is not fully understood. By studying a diverse, sympatric community of mimetic butterflies, we demonstrate that forest architecture creates a mosaic of light microhabitats that drive adaptive sensory convergence and divergence in both peripheral and central sensory systems. Our results show that across the visual system, predictable patterns of evolution characterize how species adapt to the availability of sensory information within their preferred light microhabitat. Our study provides an example of how visual systems consistently respond to their external sensory world, and illustrates the wide-reaching consequences of interspecific mutualisms, such as Müllerian mimicry, on organismal evolution.